Research on the Emotions Based on Brain-Computer Technology: A Bibliometric Analysis and Research Agenda - Yan, Wei; Liu, Xiaoju; Shan, Biaoan; Zhang, Xiangxian; Pu, Yi (Frontiers in Psychology, 2021)
This study conducts a scientific analysis of 249 literature on the application of brain-computer technology in emotion research. We find that existing researches mainly focus on engineering, computer science, neurosciences neurology and psychology. Peoples R China, USA and Germany have the largest number of publications. Authors can be divided into four groups: rtfMRI (real-time functional magnetic resonance imaging) research group, BCI (brain-computer interface) impact factors analysis group, BCMI (brain-computer music interfacing) group and user status research group. Clustering results can be divided into 5 categories, including external stimulus and ERP (event-related potential), EEG (electroencephalography) and information collection, SVM (support vector machine) and information processing, deep learning and emotion recognition, neurofeedback and self-regulation. Based on prior researches, this study points out that individual differences, privacy risk, the extended study of BCI application scenarios and others deserve further research.